New approach to calculate the true-coincidence effect of HpGe detector - Alnour, I.A.; Wagiran, H.; Ibrahim, N.; Hamzah, S.; Siong, W.B.; Elias, M.S. (American Institute of Physics Inc., 2016)
The corrections for true-coincidence effects in HpGe detector are important, especially at low source-todetector distances. This work established an approach to calculate the true-coincidence effects experimentally for HpGe detectors of type Canberra GC3018 and Ortec GEM25-76-XLB-C, which are in operation at neutron activation analysis lab in Malaysian Nuclear Agency (NM). The correction for true-coincidence effects was performed close to detector at distances 2 and 5 cm using 57Co, 60Co, 133Ba and 137Cs as standard point sources. The correction factors were ranged between 0.93-1.10 at 2 cm and 0.97-1.00 at 5 cm for Canberra HpGe detector; whereas for Ortec HpGe detector ranged between 0.92-1.13 and 0.95-100 at 2 and 5 cm respectively. The change in efficiency calibration curve of the detector at 2 and 5 cm after correction was found to be less than 1%. Moreover, the polynomial parameters functions were simulated through a computer program, MATLAB in order to find an accurate fit to the experimental data points.